1968
DOI: 10.1111/j.1476-5381.1968.tb07049.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of guanethidine on the blood pressure response to splanchnic nerve stimulation in the rat: role of the adrenal medulla

Abstract: 1. Splanchnic nerve stimulation provokes a larger increase in blood pressure in intact rats than in rats previously demedullated by means of expression of the adrenals in situ and adrenalectomy followed by adrenocortical grafting. 2. Rats pretreated with guanethidine showed an attenuated albeit prolonged hypertensive response to splanchnic stimulation. Similar effects were exerted by guanethidine in rats demedullated by expression. In rats demedullated by grafting, smaller doses of guanethidine induced a more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The present experiments have shown that the initial vasoconstrictor response does not quantitatively influence the second component caused by the release of medullary amines. This represents a definite improvement over direct splanchnic nerve stimulation which, in the rat, has been shown to cause wide-spread neurogenic vasoconstriction (Carpi & Cartoni, 1968). Indeed, guanethidine reduced the response to splanchnic nerve stimulation indicating that the neurogenic vasoconstrictor component was so extensive as to preclude any precise quantitation of the catecholamines released from the adrenal medulla.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The present experiments have shown that the initial vasoconstrictor response does not quantitatively influence the second component caused by the release of medullary amines. This represents a definite improvement over direct splanchnic nerve stimulation which, in the rat, has been shown to cause wide-spread neurogenic vasoconstriction (Carpi & Cartoni, 1968). Indeed, guanethidine reduced the response to splanchnic nerve stimulation indicating that the neurogenic vasoconstrictor component was so extensive as to preclude any precise quantitation of the catecholamines released from the adrenal medulla.…”
Section: Discussionmentioning
confidence: 86%
“…However, splanchnic nerve stimulation also evokes a neuronally mediated vasoconstrictor response in the splanchnic vascular bed which forms a considerable component of the blood pressure response in the rat. In adrenalectomized rats with grafts of adreno-cortical tissue (Carpi & Cartoni, 1968) the blood pressure responses to low frequency splanchnic nerve stimulation remained unaltered, while at higher frequencies, they were still 60 to 65% of that obtained in the intact control rats. In the present work the blood pressure response to direct electrical stimulation of the whole adrenal gland of pithed rats was analyzed for its usefulness as an indicator of adrenomedullary hormone release without interference by vasoconstrictor neurones.…”
Section: Introduction Methodsmentioning
confidence: 87%
See 2 more Smart Citations